2022
DOI: 10.1002/admi.202201200
|View full text |Cite
|
Sign up to set email alerts
|

Borate‐Based Surface Coating of Li‐Rich Mn‐Based Disordered Rocksalt Cathode Materials

Abstract: With this new turnaround in the midst of energy transition, there is a strong necessity to increase the viability of LIBs, which emphasizes the importance of the discovery and development of high-energy-density cathode materials based on sustainable and abundant metals. [1] Still, layered LiCoO 2 and hexagonal (R3m) Li(Ni, Mn, Co)O 2 cathode materials are currently the most widely used systems in electrical devices. [2] However, the high cost, limited resources, and toxicity of Co will limit its further develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The ohmic internal resistance ( R s ) and CEI membrane resistance (fitted by parallel R f and CPE1) are reflected by the starting point and the arc of the high-frequency region in the Nyquist diagram. The charge transfer resistance in the electric double-layer region (fitted by the parallel of R ct and CPE2) is reflected by the low-frequency arc. , The dominant resistance comes from R ct compared to R s and R f , as shown in the fitting results of the Nyquist plots (Figure e). NM91 shows larger R ct values within 300 cycles than 91PMA-e2, confirming that the coating layer generated by PMA-e2 with the Keggin structure indeed promotes the charge transferability of the cathode.…”
Section: Resultsmentioning
confidence: 90%
“…The ohmic internal resistance ( R s ) and CEI membrane resistance (fitted by parallel R f and CPE1) are reflected by the starting point and the arc of the high-frequency region in the Nyquist diagram. The charge transfer resistance in the electric double-layer region (fitted by the parallel of R ct and CPE2) is reflected by the low-frequency arc. , The dominant resistance comes from R ct compared to R s and R f , as shown in the fitting results of the Nyquist plots (Figure e). NM91 shows larger R ct values within 300 cycles than 91PMA-e2, confirming that the coating layer generated by PMA-e2 with the Keggin structure indeed promotes the charge transferability of the cathode.…”
Section: Resultsmentioning
confidence: 90%
“…Also, the low-valent F – sets up the charge balance to favor the incorporation of Mn as Mn 2+ in the structure, allowing the Mn 4+ /Mn 2+ double-redox reaction. Particularly, previous studies showed that the composition Li 2 Mn 2/3 Ti 1/3 O 2 F (Ti33) with Ti 4+ and mixed Mn 2+/3+ in the initial state demonstrated better cycling stability. After the initial charge, this composition can deliver a discharge capacity comparable to the Li-rich layered NMC (200–220 mAh/g) , and greater than the conventional LCO (170 mAh/g) . Furthermore, a capacity retention of 190 mAh/g (∼650 Wh/kg) after 100 cycles and 136 mAh/g (∼460 Wh/kg) after 200 cycles was obtained .…”
Section: Introductionmentioning
confidence: 91%
“…In addition to the aforementioned common coating methods, there are also other novel coating methods such as spinel nano‐coating, [ 57 ] borate coating, [ 58 ] lithium‐ion conductor coating, [ 59 ] etc., which have achieved certain results and can stabilize lithium‐rich cathode materials.…”
Section: Modification Strategies For Lrm Cathode Materialsmentioning
confidence: 99%